1905 Potemkin İsyanı ve Sultan II. Abdülhamid - Saygılı, Hasip (FSM Vakıf Üniversitesi, 2016)
1905 yazı, Uzak Doğu’da Japonlar karşısında Rus ordusunun yenilgisini netleştirirken, Çarlık Rusyasında yılbaşında yeni bir aşamaya giren devrim hareketlerini de, yükseltmeye başlamıştır. Karadeniz’de isyan eden Potemkin zırhlısının oluşturduğu gerilim, Osmanlı ülkesinde tepeden tırnağa hissedilirken, Sultan Abdülhamid kuzey komşusunda çıkan krizi en az zararla atlatabilme ve bundan faydalanma yolları aramış ve bulmuştur.

As the defeat of Russian Army was getting clarified against the Japanese in the Far East in summer 1905, it also began to upgrade the revolutionary movement that drew into a new stage in the begining of the new year in Tsarist Russia. While the tension that The Battleship Potemkin generated rebelling in Black Sea, was perceived through and through in the Ottoman country, Sultan Abdulhamid II looked for a ways to overcome the crisis arisen in his northern neighbour with the least loss and benefit from it and came up with them.
Potemkin Mutiny of 1905 and Sultan Abdulhamid II
Keywords: Potemkin zırhlısı; Sultan Abdülhamid; Çar Nikola; Donanmada isyan; The battleship Potemkin; Sultan Abdulhamid II; Tsar Nicolas II; Naval mutiny